Formulation and manufacture of leaves of Vitex negundo L. in tablet dosage form - Anulude, Jonathan Ijeoma 1952-
The study was made with the aim of manufacturing stable tablets from the leaves of Vitex negundo L. The leaves were collected and evaluated for moisture content. They were dried, pulverized, and assayed for total alkaloids content. A series of formulations were prepared, tested and evaluated, employing different binding agents (acacia, corn starch, and gelatin) and disintegrating agents (corn strach, bentonite, cassava starch, and tragacanth) in varying concentrations. The wet granulation method was used for all of the formulations, and the granules were evaluated for moisture content and particle size distribution. The granules were compressed using a single-punch tablet press. The resulting tablets were evaluated for weight variation, hardness, disintegration time, and total alkaloids content. Stability studies were done by aging the tablets at room temperature for 7 months and at 45(degrees C) for one month. The binding agents and disintegrants were evaluated for their respective functions in the formulations. Acacia was found to be the best binder, while corn starch was the best disintegrant. Tablets were prepared from a particular tablet formulation and sent to the Pharmacology Department of the College of Medicine, University of the Philippines, for the continuing clinical studies.
Available to the General Public.
Thesis (Master of Science in Industrial Pharmacy)--University of the Philippines, March 1980.
Keywords: Tableting; Lagundi; Botany, Medical; Tablets (Medicine).